SYNTHESIS AND STUDY OF THE COMPLEX COMPOUND OF N-(1H-1,2,4-TRIAZOL-YL) ACETAMIDE WITH ZINC (II) CHLORIDE (Scientific journal of the Fergana State University, 2025)
Methods of synthesizing complex compounds of N-(1H-1,2,4-triazol-yl) asetamide with Zn(II) chloride was developed, and the composition and structure of the synthesized complex compounds were studied using modern physical and chemical research methods. It was found that the ligand is coordinated through the second nitrogen of the triazole ring and the oxygen atoms of the acetamide group in the reactions of N-(1H-1,2,4-triazol-yl) asetamide complex formation. [Zn(L)2(H2O)2]Cl2 crystals have a monoclinic molecular structure, in which the metal atom forms a six-membered chelate ring with the nitrogen of the triazole ring and the oxygen atoms of the acetamide group and the oxygen atoms of water. In the [Zn(L)2(H2O)2]Cl2 complex, the bond lengths of Zn1-N3, Zn1-O1 and Zn1-O2 are 1.937, 2.024 Å and 2.40 Å, and the angles of N3-Zn1-N4 are 91.32°(19). The largest angular values ​​belong to the angles of N3-Zn1-N3, O1-Zn1-O1 and N4-Zn1-N4, which are 180.0°. The coordination number of the central copper atom is six and it is hybridized in the sp3d2 state. Intermolecular hydrogen bonds are formed between the hydrogen atom of the imine group of the 3-acetylamino-1,2,4-triazole ligand and the oxygen of water. The positive charge of the zinc ion is compensated by the chloride acid ligand in the anionic state.